EVALUASI PERBANDINGAN PERESEPAN OBAT ANTIHIPERTENSI GENERIK DAN BERMEREK PADA PASIEN RAWAT INAP DI APOTEK RS ISLAM SITI HAJAR MATARAM TAHUN 2023 - Annisaturrahmah Himawan (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
Hypertension is a non-communicable disease with a high prevalence that requires long-term therapy. Rational use of antihypertensive drugs, both generic and branded, is an important aspect of healthcare services, especially for inpatients. This study aimed to evaluate the comparison between generic and branded antihypertensive drug prescriptions among inpatients at the Pharmacy of Siti Hajar Islamic Hospital Mataram in 2023. This research employed a descriptive method with a retrospective approach based on prescription data analysis. The results showed that generic drug prescriptions were more dominant than branded drugs, in line with cost-efficiency policies and the National Health Insurance program. However, branded drugs were still prescribed in certain cases requiring specific clinical considerations. In conclusion, antihypertensive prescribing patterns in the hospital tend to favor generic drugs, although branded drugs remain necessary in specific clinical situations.